- #1

- 734

- 0

however, if i differenate the 1st equation, dy/dx=v+x*dv/dx

and if i differenate the 2nd equation, dv/dx=(1/x)*dy/dx + [-1/(x^2)]y

but both differenated equations don't seem the same...

does somebody know where my calculuations went wrong?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter asdf1
- Start date

- #1

- 734

- 0

however, if i differenate the 1st equation, dy/dx=v+x*dv/dx

and if i differenate the 2nd equation, dv/dx=(1/x)*dy/dx + [-1/(x^2)]y

but both differenated equations don't seem the same...

does somebody know where my calculuations went wrong?

- #2

Astronuc

Staff Emeritus

Science Advisor

- 19,961

- 3,492

becomes x (dv/dx) = dy/dx - y/x, but v = y/x

so x (dv/dx) = dy/dx - v

or

x (dv/dx) + v = dy/dx, which is same as other equation.

- #3

- 734

- 0

thank you very much!!! :)

Share: